2005
DOI: 10.1186/bcr999
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in genes involved in estrogen and progesterone metabolism and mammographic density changes in women randomized to postmenopausal hormone therapy: results from a pilot study

Abstract: IntroductionMammographic density is a strong independent risk factor for breast cancer, and can be modified by hormonal exposures. Identifying genetic variants that determine increases in mammographic density in hormone users may be important in understanding hormonal carcinogenesis of the breast.MethodsWe obtained mammograms and DNA from 232 postmenopausal women aged 45 to 75 years who had participated in one of two randomized, double-blind clinical trials with estrogen therapy (104 women, taking 1 mg/day of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 38 publications
(27 reference statements)
0
32
0
Order By: Relevance
“…7 A report that included women from two trials found that postmenopausal women randomly assigned to 1 mg/d of micronized 17␤-estradiol (n ϭ 104) had an adjusted absolute mean increase in mammographic density of 4.6% after 12 months versus a 0.02% increase in women assigned to placebo (n ϭ 93). 25 Our finding of a 2.6 percentage point difference in percent density in women randomly assigned to CEE versus placebo is lower than the 6.9 percentage point difference observed for CEE plus MPA 2.5 mg/d in WHI, where CEE plus MPA increased percent density by a mean of 6.0 percentage points (95% CI, 4.6 to 7.5) at year 1 compared with a mean decrease of 0.9 percentage points (95% CI, Ϫ0.2 to Ϫ1.5) in the placebo group (P Ͻ .001), with differences largely persisting after 2 years. These results suggest a sizeable role for progestin on mammographic density, but our results suggest that CEE alone also can influence mammographic density.…”
Section: Discussionmentioning
confidence: 99%
“…7 A report that included women from two trials found that postmenopausal women randomly assigned to 1 mg/d of micronized 17␤-estradiol (n ϭ 104) had an adjusted absolute mean increase in mammographic density of 4.6% after 12 months versus a 0.02% increase in women assigned to placebo (n ϭ 93). 25 Our finding of a 2.6 percentage point difference in percent density in women randomly assigned to CEE versus placebo is lower than the 6.9 percentage point difference observed for CEE plus MPA 2.5 mg/d in WHI, where CEE plus MPA increased percent density by a mean of 6.0 percentage points (95% CI, 4.6 to 7.5) at year 1 compared with a mean decrease of 0.9 percentage points (95% CI, Ϫ0.2 to Ϫ1.5) in the placebo group (P Ͻ .001), with differences largely persisting after 2 years. These results suggest a sizeable role for progestin on mammographic density, but our results suggest that CEE alone also can influence mammographic density.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7]. Although a few genetic variants have been identified (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19), the exact genetic determinants of MD are however not clear.…”
Section: Introductionmentioning
confidence: 99%
“…47). Several other genetic variants have been found to interact with EPT (8,10,14). Given that EPT use has strong effects on MD in some, but not all women (35), these gene-environment interactions reported from several studies could represent real effects.…”
Section: Introductionmentioning
confidence: 99%
“…Haiman et al examined whether polymorphisms in genes involved in steroid hormone biosynthesis and metabolism were related to density (11). In 2005, the same group conducted a further study of women from a randomized controlled trial of estrogen therapy (12). Maskarinec et al (13) examined premenopausal women for several polymorphisms.…”
Section: Introductionmentioning
confidence: 99%